Design of Ka-band thin film power divider based on multi-line gap coupling - Xu Muhua; Zhou Yujin; Li Shuaishuai; Gu Jiangchuan; Zhou Jun; Shen Ya (Dianzi Jishu Yingyong)
The traditional power divider structure is difficult to meet the requirements of high frequency and miniaturization of microwave systems due to obvious high-frequency crosstalk and large volume of impedance conversion lines. To solve this problem, this paper proposes a Ka-band power divider based on multi-line slit coupling structure. Starting from the circuit topology, the circuit design, modeling simulation and experimental verification of the device are carried out. The test results show that the device has good high-frequency performance and shows the filtering response with propagation zeros on both sides of the pass-band, which realizes the design of thin-film power divider with multi-wire gap coupling.